Environmental and resource footprints in a global context: Europe's structural deficit in resource endowments. (September 2016) - Tukker, Arnold; Bulavskaya, Tanya; Giljum, Stefan; de Koning, Arjan; Lutter, Stephan; Simas, Moana; Stadler, Konstantin; Wood, Richard
Highlights: Resource-efficiency and circularity is becoming an important policy topic globally and in the EU. The EU's resource-efficiency roadmap recognizes the relevance of consumption-based accounting for carbon, water, land and materials. Using the MRIO with the highest, consistent sector and product detail available (EXIOBASE), for the first time we analyse the carbon, water, land and materials footprint of countries side-by-side. We show that Europe, as the only region on the world, has a negative import/export balance for embodied imports of all footprints – Europe lives on resource and emission credits provided by other parts of the world. Reductions of footprints are hence particularly relevant for Europe. Abstract: The European Union (EU) has proposed in its Resource-efficiency roadmap a 'dashboard of indicators' consisting of four headline indicators for carbon, water, land and materials. The EU recognizes the need to use a consumption-based (or 'footprint') perspective to capture the global dimension of resources and their impacts. In this paper, we analyse how the EU's footprints compare to those of other nations, to what extent the EU and other major economies of the world rely on embodied resource imports, and what the implications are for policy making based on this comparison. This study is the first comprehensive multi-indicator comparison of all four policy relevant indicators, and uses a single consistent global Multi-Regional Input Output (MRIO) database with a unique and high level of product detail across countries. We find that Europe is the only region in the world that relies on net embodied imports for all indicators considered. We further find that the powerful economies of China and others in the Asia-Pacific already dominate global resource consumption from a footprint perspective, while they still haven't reached the prosperity of developed countries. Competition for resources is hence likely to increase, making Europe even more vulnerable. A hot spot analysis suggests that final consumption of food, transport and housing are priorities for reduction efforts along the life cycle. Further, countries with a similar Human Development Index can have very different footprints, pointing at societal organisation at macro-level as option for improvement. This points at options for countries for lowering their footprint, becoming less dependent on embodied imports, while maintaining a high quality of life.